Introduction of web based e-learning in pharmacology: an innovative way - Barvaliya, Manish; Anovadiya, Ashish; Purohit, Bhargav M. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: In current scenario, poor attendances in classes and poor performances of students are a stimulus to think beyond the conventional teaching approach. Being current digital generation, students may show their affection to e-learning. Aim of this study was to introduce the e-learning in Pharmacology with objectives to evaluate its acceptability by students and faculties and learning gain of students Methods: Four inter-related e- modules for a topic “drugs used in treatment of bronchial asthma” were prepared and provided to the students. Pre-test was conducted before giving E-modules. Students were instructed to complete the e-modules in seven days and post-test was conducted on last day. Feedbacks from students and faculties were collected. Learning gain of students was evaluated along with their acceptability for e-modules. Results: Total of 147 students participated in the study but, 130 students completed pre-test and post-test, both. The absolute learning gain (% post-test score - % pre-test score) was found 23.3±19.2%. The class average normalized learning gain was found 0.32 (32%) that was significant, as per Hake’s criteria for the effectiveness of educational interventions. Slow speed of internet, background noise in modules, and size of e-modules were some technical problem faced by students. The most of students perceived the modules positively and demanded the e-modules for other topics. The faculties also perceived it positively and suggested to use e-modules additionally to classroom lectures. Conclusions: E-learning modules were taken positively by students and faculties and resulted in significant learning gain.